Germination and regeneration mechanisms in Mediterranean degenerate forests - Bacilieri, R.; Bouchet, M. A.; Bran, D.; Grandjanny, M.; Maistre, M.; Perret, P.; Romane, F. (Journal of Vegetation Science, 1993)
Abstract. Germination and developmental behaviour during juvenile stages are of importance in relation to succession mechanisms acting on plant communities. This is particularly so in the Mediterranean region, where the climatic summer drought causes stress. We investigated and compared germination and development of four tree species in two parts of the French Mediterranean region where the original dominant tree species (Quercus pubescens) has been largely replaced by Quercus ilex in the southern part, and Castanea sativa in the northern part. Observed differences in germination rates and developmental behaviour, especially shootroot ratio and the role of water supply, suggest that other species may eventually replace the current dominant species.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Castanea sativa; Pinus pinaster; Quercus ilex; Quercus pubescens

Dynamics of holm oak (Quercus ilex L.) coppices after clearcutting in southern France - Floret, C.; Galan, M. J.; Floc'h, E.; Romane, F. (Plant Ecology, 1992)
Holm oak (Quercus ilex L.) forest is one of the most widespread biocoenoses in the southern part of France. Until recently, clearcutting of wood for domestic use was carried out every 20 years or so in these coppice stands. In order to study coppice stand dynamics after cutting this paper presents results of observations of some items describing the vegetation structure, the floral composition, and the life cycles in a holm oak coppice stand during a six year period after clearcutting. One of the questions addressed in this study was whether these coppice stands reach a 'steady' state based on auto-succession, or if they continue to change. The results of the floristic changes after cutting suggest that the model of auto-succession best fits with the vegetation dynamics, even if changes in the density and life cycles of herbaceous species still exist six years after clearcutting.
Keywords: Life cycles; Mediterranean climate; vegetation succession